Approaches to reduce noise from ships operating in important killer whale habitats. (February 2019) - Williams, Rob; Veirs, Scott; Veirs, Val; Ashe, Erin; Mastick, Natalie
Abstract: Shipping is key to global trade, but is also a dominant source of anthropogenic noise in the ocean. Chronic noise from ships can affect acoustic quality of important whale habitats. Noise from ships has been identified as one of three main stressors–in addition to contaminants, and lack of Chinook salmon prey–in the recovery of the endangered southern resident killer whale (SRKW) population. Managers recognize existing noise levels as a threat to the acoustical integrity of SRKW critical habitat. There is an urgent need to identify practical ways to reduce ocean noise given projected increases in shipping in the SRKW's summertime critical habitat in the Salish Sea. We reviewed the literature to provide a qualitative description of mitigation approaches. We use an existing ship source level dataset to quantify how some mitigation approaches could readily reduce noise levels by 3–10 dB. Highlights: Ship noise can degrade critical habitat of endangered whales. It is important to reduce ship noise to improve the ability of critically endangered killer whales to hunt salmon. We review ship noise mitigation approaches. Mitigation approaches could readily reduce noise levels by 3–10 dB.